Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)
fs-ref-orig: Bouchard, L., Batista, R. et Reaume, M. (2021). Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2021a

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)
fs-ref-orig: Ontario mental health & addictions virtual care collaborative. (2021). Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication]. Centre for Addiction and Mental Health (CAMH). fs-code-orig: Ontario mental health & addictions virtual care collaborative-2021

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Quebec’s English-speaking community and the partnership approach of its networks in health - Pocock, Joanne (Linguistic Minorities and Society, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted. Keywords: official language minority communities, intersectoral partnerships, access to public health care, language policy, community-based participatory evaluation (CBPE)

Améliorer l’état de santé des francophones de Terre Neuve-et-Labrador - Réseau Santé en français de Terre-Neuve-et-Labrador (2021)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

Pour une réforme de la santé respectueuse des deux communautés linguistiques officielles. Mémoire présenté à l’honorable Dorothy Shephard, ministre de la Santé, dans le cadre de la consultation publique sur l’avenir des soins de santé dans la province du Nouveau-Brunswick - Société de l'Acadie du Nouveau-Brunswick (2021)

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)
fs-ref-orig: Thifault, M.-C. et LeBel, M. (2021). Dérives : une histoire sensible des parcours psychiatriques en Ontario français. Les Presses de l'Université d'Ottawa. fs-code-orig: Thifault-2021